Rheumatological manifestations in patients hospitalized with COVID-19 in a tertiary care setting - Hassan Mustafa, Syed; Umer Farooq, Muhammad; Iqbal, Farah; Alam, Muhammad Adeel; Ullah, Ihsan; Adeeb, Humera (Journal of Ayub Medical College Abbottabad, 2021)
Background: Corona virus disease 2019 (COVID-19) is a pandemic affecting over 150 million people worldwide since its emergence in Wuhan, China in December 2019, and is leading to over 600 thousand deaths. Severe acute respiratory syndrome novel coronavirus 2 (SARS-nCoV-2) causes a wide range of symptoms by affecting different organ systems of the body. This study was designed to specifically look for its rheumatological manifestations. Methods: It was a cross-sectional study conducted in the corona complex MTI Lady Reading Hospital Peshawar. A total of 141 COVID-19 positive hospitalized patients requiring oxygen therapy and having no previous rheumatological diseases were enrolled and studied for any rheumatological manifestations. Results: There were 88 (62.4%) males and 53 (37.6%) females, with age range from 27-88 years, and mean age of 58.5±11.5 SD. Arthralgia and myalgia were found very common, occurring in 128 (90.8%) and 119 (84.4%) of patients. Arthritis was not found in any patient. Conclusion: Arthralgia and myalgia were reported frequently in patients with severe COVID-19 requiring oxygen therapy, while arthritis was not present even in a single patient as is reported in other viral infections. Keywords: Arthralgia, Arthritis; COVID-19; Myalgia; Rheumatological Manifestations